Cost and performance of some carbon capture technology options for producing different quality CO2 product streams - Porter,RTJ; Fairweather,M; Kolster,C; Mac,Dowell N; Shah,N; Woolley,RM (International Journal of Greenhouse Gas Control, 2016)
A techno-economic assessment of power plants with CO2 capture technologies with a focus on process scenarios that deliver different grades of CO2 product purity is presented. The three leading CO2 capture technologies are considered, namely; oxyfuel combustion, pre-combustion and post-combustion capture. The study uses a combination of process simulation of flue gas cleaning processes, modelling with a power plant cost and performance calculator and literature values of key performance criteria in order to evaluate the performance, cost and CO2 product purity of the considered CO2 capture options. For oxyfuel combustion capture plants, three raw CO2 flue gas processing strategies of compression and dehydration only, double flash system purification and distillation purification are considered. Analysis of pre-combustion capture options is based on integrated gasification combined cycle plants using physical solvent systems for capturing CO2 and sulfur species via three routes; co-capture of sulfur impurities with the CO2 stream using Selexol™ solvent, separate capture of CO2 and sulfur impurities using Selexol™, and Rectisol® solvent systems for separate capture of sulfur impurities and CO2. Analysis of post-combustion capture plants was made with and without some conventional pollution control devices. The results highlight the wide variation in CO2 product purity for different oxyfuel combustion capture scenarios and the wide cost variation for the pre-combustion capture scenarios. The post-combustion capture plant with conventional pollution control devices offers high CO2 purity (99.99 mol%) for average cost of considered technologies. The calculations performed will be of use in further analyses of whole chain CCS for the safe and economic capture, transport and storage of CO2.